Proses Pembelajaran Berbasis Online pada Siswa Kelas Tinggi di Masa Pandemi Covid-19 - Khusnul Khotimah; Andi Prastowo (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2022)
Dissemination of the Covid-19 pandemic has impacted various in human life sectore. One of the one most an influenced is field of education. This discussion intend to reveal about online-based learning process during the pandemic in high class at Daarul Huda Islamic Elementary School Tangerang city along with the obstacles that occur during online learning and what efforts can minimize these obstacles. Online learning used within this disccus is the use of existing applications on smartphones, laptops and computers. Qualitative approach with case study method used by researcher to solve this problem and by using a descriptive design conducted at the Daarul Huda Islamic Elementary School in Tangerang, involving 3 students and 3 teachers as informants. Data collection was obtained based on observations and interviewr carried out in a structured manner with question that have been compile and linked and developed with related literature. This study show the results that online-based learning process at Daarul Huda Islamic Elementary School can run smoothly, but it is felt that most teachers and students are less effective than conventional face-to-face learning.